2017
DOI: 10.1111/jdv.14714
|View full text |Cite
|
Sign up to set email alerts
|

Novel device‐based acne treatments: comparison of a 1450‐nm diode laser and microneedling radiofrequency on mild‐to‐moderate acne vulgaris and seborrhoea in Korean patients through a 20‐week prospective, randomized, split‐face study

Abstract: Both DL and FMR demonstrated efficacies for acne and seborrhoea, with reasonable safety profile. FMR was more effective than DL for the long-term maintenance, and subjective assessments for texture and scar improvements. Therefore, a few sessions of these devices would be a viable option for acne treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 38 publications
1
52
0
Order By: Relevance
“…Screening of the reference lists of these papers resulted in one additional study, making the total 255. Of these 254 were excluded …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening of the reference lists of these papers resulted in one additional study, making the total 255. Of these 254 were excluded …”
Section: Resultsmentioning
confidence: 99%
“…Studies that only used the PROM as an outcome measurement instrument were excluded, but study details were tabulated, per protocol. We identified 188 studies that reported treatment satisfaction as an outcome: 91 on treatment of acne 68–158 and 97 on treating acne scars (a possible sequela of acne) 159–255 . These numbers show that clinicians and researchers do consider treatment satisfaction as an important outcome.…”
Section: Resultsmentioning
confidence: 99%
“…A similar effect was found in our study; as the number of treatments increased, both radiofrequency instruments were able to improve active acne. Several studies have explored the mechanism of radiofrequency treatment for the treatment of active acne, which may include heat generated by radiofrequency inducing thermal denaturation of the peri‐hair follicle collagen, hair follicle, and sebaceous gland and killing of C acnes , the pathogenic factor in the development of acne vulgaris.…”
Section: Discussionmentioning
confidence: 99%
“…Fractional microneedling radiofrequency has been recently reported to improve acne, acne scar, and wrinkle. 23 It delivers bipolar radiofrequency directly to the dermis with minimal epidermal damage, resulting in dermal heating. The heat produced by the radiofrequency device originates from electron movement and conductivity of the target tissue.…”
Section: Discussionmentioning
confidence: 99%